NOTES ON HELLENISTIC TEXTS - White, Heather (Myrtia, 1998)
The present work consists of several notes on Hellenistic texts, particularly on AP . VI 296; VII 44; V 55; VII 489; VII 656; IX 21; IX 330; IX 339; XIII 26 y Theoc. Id . 18.